Experts in the Formation of Public Politics: Criminological Knowledge and the Future of Juvenile Justice Reform - Zdanevičius, Arnas (Sociologija. Mintis ir veiksmas, 2002)
The aim of this paper was to acquire a deeper understanding of the processes during which a construction of criminological knowledge is taking place and to analyse the complex relationships between experts and other agents in the formation of a particular task, that of juvenile criminal justice reform. Juvenile justice is regarded as one of the components of the Lithuanian criminal justice policy. Juvenile justice as a public policy is closely linked to various groups of experts such as lawyers, criminologists, police administrators, social workers, etc. My intention was to examine ways by which criminological knowledge has been mobilised by the Lithuanian political authorities when tasks are allocated to experts. An analytical theoretical model of public policy that included analysis at three levels (state, professionals and individual) illustrates a process during which the state mobilises criminological knowledge and certain professional groups monopolise spheres of influence. Qualitative methods (semi-structured interviews with experts), document analysis and secondary data served as major sources for the analysis of this case study. Knowledge-power discourse as a Foucaultian truism about criminology's utility to power sheds light on the mutual relationship and interaction between academics and policy makers. This relationship has yet to become a research agenda in post-soviet societies. A case-study of the Lithuanian juvenile justice reform demonstrates that criminology as a discipline is being institutionalised and is achieving an advisory role in the decision making process. On the one hand, the close connection to power creates favourable conditions for applications of legitimised academic knowledge, which consequently can encourage social change and reform. On the other hand, the adaptation of academic knowledge to that of powerful groups strengthens the historical tendency in criminology, that is, to become merely administrative and utilitarian to power.
Keywords: expert; public politics; private interests; criminological knowledge; juvenile justice